Conceptual design of a telecommunications equipment container for humanitarian logistics - Stella Parisi; Charisios Achillas; Dimitrios Aidonis; Dimitrios Folinas (International Journal of Business Science & Applied Management (IJBSAM), 2016)
Preparedness addresses the strategy in disaster management that allows the implementation of successful operational response immediately after a disaster. With speed as the main driver, product design for humanitarian aid purposes is a key factor of success in situations of high uncertainty and urgency. Within this context, a telecommunications container (TC) has been designed that belongs to a group of containers that serve the purpose of immediate response to global disasters. The TC includes all the necessary equipment to establish a telecommunication centre in the destroyed area within the first 72 hours of humanitarian operations. The design focuses on defining the topology of the various parts of equipment by taking into consideration factors of serviceability, functionality, human-product interaction, universal design language, energy consumption, sustainability and the interrelationship with the other containers. The concept parametric design has been implemented with SolidWorks CAD system.
Keywords: 650; case study; design; telecommunications container